Traditional uses of wild medicinally important plants of Batkhela, kpk, Pakistan - Fayaz Ali; Imran Khan; Shariat Ullah; Mohammad Ihsan; Amir Abdullah Khan (International Journal of Phytomedicine, 2017)
The present study was carried out in Sangina valley of Batkhela, Malakand District, Khyber Pakhtunkhwa Pakistan. The aim of the current work was the documentation of plants utilized by the local inhabitants for different medicinal purposes. Majority of cases utilized same plant species in several ways for distinct remedies. After collecting informations through an open-ended questionnaire, totality of 46 plant species used for different medicinal purposes were recorded in the study area belonging to 31 families. Family Lamiaceae ranked as top by contributing 10.86% to the total documented medicinal plant species in the studied area. Family Euphorbiaceae and family Solanacaea shares individually 8.69% and 6.52% to the total, followed by Family Mimosaceae, Asteraceae, Moraceae and family Polygonaceae each having a contribution of 4.34%. Of total 46 reported plant species, 12 plant species were used as diuretic, 8 species were found good as tonic, 7 plant species were significant in curing of cough and 6 plant species were used for remedy of stomach pain. 5 plant species each were used for curing of fever, diarrhea and dysentery.